The Effect of Using Fun Active Learning Strategy and Visualization Strategy on Speaking Ability in the 7th Graders of Junior High School - Sinambela, Erika; Milala, Herian Bastanta; Pasaribu, Arsen Nahum; Manik, Sondang; Manurung, Lastri Wahyuni (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this research is to describe the problem of speaking ability in junior high school needs to be done to observe the development of students'' learning difficulties incurrents speaking skills. This research is a collaborative classroom action research. That is, the researchers did not conduct their own research, but collaborated or collaborated with the school, namely the class VIII teacher at SMP Negeri 3 Binjai. Based on the results of the pre-test, the pre-test mean score was 58,65 and the mean score in the post-test was 73,78. It can be seen that the students'' skill in speaking by using storytelling technique increased. From these calculations, it can be inferred that there was a difference of students'' scores before and after receiving the treatment. Consequently, these data which had been analyzed answered the first research question that using visualization startegy can improve student speaking ability at SMP Negeri 3 Binjai at 7th graders. Based on the data analysis, the researcher found that Visualization strategy can improve students’ skill in speaking. As the result from the pre-test and post-test mean scores which were given. The improvement of mean score was 55 to 96. It means that there is significant difference of achievement between the students who were taught by using Visualization Strategy and Fun Active Learning Strategy and the students who were taught with conventional method. The data also showed that students felt that storytelling technique could help them in speaking. Most of them also responded that they attempt to use Visualization Strategy in their daily speaking.